Análise do alinhamento entre os sistemas de medição de desempenho e as práticas de produção enxuta: um estudo de caso em uma empresa calçadista - Arnaud, Leonardo de Miranda (2013)
Lean production a rational method to manufacture products also promotes greater interaction and integration between various parts, from the processing of material to the processes between suppliers and industry. This condition is especially due to the configuration of lean tools and practices, leading to the emergence of changes in procedures and the way people work providing a decentralization in decision making. The Performance Measurement Systems (PMS) are a fundamental part of this transformation, as they facilitate the coordination and synchronization of activities and processes. However, considering the applicability of lean production in organizations, it is clear that many companies fail to achieve any return of this development potential due to lack of adequate procedures to assess the actual benefits achieved or because the actions to be taken are not explained well in the search for satisfactory results . This lack of alignment between the assessment methods (PMS) and the appropriate actions (lean practices) promotes a lack of synchronization and unsustainability of the program. Therefore, this dissertation aims to analyze the alignment between system performance measurement and lean practices in a company in the footwear sector in order to contribute to the knowledge of the factors that ensure the maintenance of this management model. To survey the lean practices and measures (indicators) semi-structured interviews were conducted subsidized on a check-list and interview scripts. For the analysis and presentation of data, adopted practices and indicators structure have been detailed and for the alignment analysis a matrix of relationships have been employed. The results showed that the strong links between the measures (indicators) and the practices occur in a timely manner which makes the alignment flawed. This display conveys that the practices were developed to meet specific needs, so that the performance of a practice does not influence the other, in addition, it was noticed that few indicators support lean practices, which opposes the essence of lean model that advocates the payment and interrelation of parts.